THE INFLUENCE OF E-WOM, HEDONIC SHOPPING AND SALES PROMOTION ON IMPULSE BUYING IN ONLINE RETAIL INSURANCE PRODUCT PURCHASE DECISIONS IN INDONESIA - Syukur Abdullah; Ngadino Surip Diposumarto; Hari Muharam (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to describe the influence of electronic word of mouth (e-WOM), hedonic shopping, and sales promotion on purchasing decisions for online retail insurance products, with impulse buying as a mediating variable. The method used is quantitative descriptive, which aims to describe phenomena objectively based on numerical data without testing hypotheses. The population of the study was customers of general insurance companies who purchased retail insurance products online, with an estimated population of around 500,000 people. The sample was taken using a purposive sampling technique based on certain criteria, and 400 respondents were determined using the Slovin formula. Data collection was carried out through observation, interviews, documentation, and distributing questionnaires as the main instrument to measure consumer perceptions of the variables studied. Data analysis was carried out using descriptive statistical methods and Structural Equation Modeling (SEM) with the help of Lisrel 8.88 software. The results of the study showed that e-WOM, hedonic shopping, and sales promotion had a significant influence on impulse buying. Impulse buying was proven to have a significant influence on purchasing decisions for online retail insurance products. Simultaneously, the four variables also had a significant influence on purchasing decisions. The impulse buying variable acts as a full mediator in the relationship between e-WOM and hedonic shopping on purchasing decisions, as well as a partial mediator between sales promotion and purchasing decisions. These findings indicate that an effective digital marketing strategy needs to consider the combination of credible e-WOM, a pleasant shopping experience, attractive sales promotions, and consumer impulsiveness as the key to driving online retail insurance product purchasing decisions in the digital era.